HAKIKAT PENDIDIKAN MANUSIA DI ERA DIGITAL : TINJAUAN ONTOLOGIS FILSAFAT PENDIDIKAN - Aulia Damayanti; Abdul Khobir; Muntaqo Fadli; Nisrina Qurrotul Ain; Rahma Nafalina Azzahra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the essence of human education in the digital era from an ontological perspective. Using a qualitative descriptive-analytical method based on credible academic sources, the research analyzes how digitalization reshapes human identity, learning patterns, and educational paradigms. The findings show that technology increases access and flexibility but also raises concerns about dehumanization, ethical issues, and declining moral awareness. Ontologically, humans remain rational, moral, social, and spiritual beings whose integrity must be preserved amid technological change. The study concludes that education in the digital age must balance technological innovation with humanistic and spiritual values to ensure holistic human development and maintain human dignity.